Kinetic progress in post-synthetic doping of 2D perovskite nanoplatelets. (4th May 2021) - Zhang, Ruohu; Qu, Junfeng; Chen, Zizi; Wang, Chunlei; Xu, Shuhong
Abstract: Room-temperature post-synthetic doping in perovskite has drawn much attention for its looser condition and controllable doping. Compared with direct synthesis, the kinetic progress in post-synthetic doping is unique and may provide new methods for the manipulation of doping. In this work, the kinetic progress during post-synthetic doping in 2D perovskite nanoplatelets (NPLs) is studied. It was found that in spite of the feeding ratio, the concentration of dopant precursor can also affect post-synthetic doping progress. Afterwards, Mn was doped into 2D perovskite NPLs through fixed-volume doping and fixed-concentration doping for comparison and both methods can realize white-light emission.